Industrial training final report: Bahagian Pengurusan Fasiliti UiTM Permatang Pauh / Muhammad Aqil Fikri Abdul Muis - Abdul Muis, Muhammad Aqil Fikri (Universiti Teknologi MARA, Pulau Pinang, 2024)
The Facility Management Office has experienced several phases of transformation throughout its history. It was first established in 1972 as the Office of Local Engineers, before evolving into the Department of Development and Maintenance in 1982. By 1994, it became the Office of Development and Maintenance. On September 15, 1995, recognizing the expanding responsibilities of both the Development and Maintenance Offices, they were reorganized and placed under the Chancellor's Office as separate entities to better manage their growing roles. The declaration of UITM as MARA Technology University in August 1999 further expanded the Maintenance Office's scope, aligning it more closely with the university's broader development efforts. In alignment with the vision of MARA University of Technology to achieve world-class recognition as a public institution, the Maintenance Office underwent a major restructuring and rebranding on January 4, 2006, becoming the Office of Facility Management. At the Permatang Pauh Campus, the Facility Management Office is divided into several specialized units, including the Administrative, Council, Project, Public, Electrical, and Mechanical units.